Combating wildlife crime - Sellar, John M. (Henry Stewart Talks, 2008)
CITES, The convention regulating trade in endangered species, Illegal trade, The wildlife that is traded illegally, how it is traded and its markets, Organized crime, Indicators of organized crime and criminal networks, Responses, What needs to be done and what is being done
Archived at 2022/04/03